2017
DOI: 10.1186/s13287-017-0517-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic population derived from human pluripotent stem cells is effectively increased by selective removal of undifferentiated stem cells using YM155

Abstract: BackgroundPluripotent stem cells (PSCs) such as embryonic stem cells and induced pluripotent stem cells are promising target cells for cell regenerative medicine together with recently advanced technology of in-vitro differentiation. However, residual undifferentiated stem cells (USCs) during in-vitro differentiation are considered a potential risk for development of cancer cells and nonspecific lineage cell types. In this study we observed that USCs still exist during hepatic differentiation, consequently res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…It has recently been reported that during hepatocyte differentiation, treatment with YM155, which is known to induce selective and complete cell death of undifferentiated hiPSCs, improved the quantity and quality of induced hepatocytes and consequently eliminated the possibility of teratoma formation [43]. Based on these observations, and our present findings, differentiation protocols can be devised to obtain safe cell sources with no risk of teratoma formation.…”
Section: Discussionsupporting
confidence: 79%
“…It has recently been reported that during hepatocyte differentiation, treatment with YM155, which is known to induce selective and complete cell death of undifferentiated hiPSCs, improved the quantity and quality of induced hepatocytes and consequently eliminated the possibility of teratoma formation [43]. Based on these observations, and our present findings, differentiation protocols can be devised to obtain safe cell sources with no risk of teratoma formation.…”
Section: Discussionsupporting
confidence: 79%
“…By correlating the hPSC scores with the sensitivities of each cell line to each of 543 compounds, we identified YM155 as the most effective drug in cells with high hPSC scores (Fig. 1B); this implies that YM155 should be highly specific for hPSCs, as demonstrated previously (Bedel et al, 2017; Kang et al, 2017; Kim et al, 2017; Lee et al, 2013b). Based on correlation of drug and gene expression signature (Fig.…”
Section: Resultssupporting
confidence: 72%
“…To address this danger, several approaches have been developed for selective removal of residual hPSCs (Jeong and Cha, 2017). For example, we previously reported that YM155, a survivin inhibitor developed as an anti-cancer drug, is selectively cytotoxic against undifferentiated hPSCs and inhibits teratoma formation (Lee et al, 2013b), and this finding has been reproduced in several independent studies (Bedel et al, 2017; Kang et al, 2017; Kim et al, 2017). At that time, however, the molecular mechanism underlying the high susceptibility of hPSCs to YM155 had not been fully elucidated.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Con#23 Con#26 Conversely, STRAP loss increased most liver differentiation related genes, such as ALB, AFP, and HNF4A (35,36), in Huh6 and more obviously in Huh7 cells ( Supplementary Fig. S6B).…”
Section: Con#11mentioning
confidence: 99%